Acute pain services in India: A glimpse of the current scenario - Parmanand N Jain; Sumitra G Bakshi; Raghu S Thota (Wolters Kluwer Medknow Publications, 2015)
Background & Aims: Acute postoperative pain is still a neglected and unresolved issue in day to day practice. Acute pain services were conceived three decades ago to form a dedicated team to monitor pain assessment and treatment as per laid down pain protocols and guidelines. The concept of acute pain service (APS) is slowly evolving in India. Materials and Methods: This nationwide questionnaire survey was conducted to identify the status of postoperative pain, the prevalent treatment practices, opioid policy and the prevalence of acute pain services in India. An electronic communication was sent to 4000 Indian Society of Anesthesiologists life members. Results: We received only 146 responses mainly from faculties/consultants from few corporate hospitals or medical colleges. About 68 APSs are functioning, however, 20 APS do not have any training programs and 34 have no written protocols. Anesthesiologists are involved in postoperative pain management only when epidural analgesia is employed; otherwise surgeons are custodians of pain in the ward. Conclusion : This survey found that majority of anesthesiologists are agreeable to forming an APS and ready to take the responsibility, however administrative issues seem to be a major barrier.